Avoidant/Restrictive Food Intake Disorder (ARFID) - Lily Tucciarone; Sara Murphy; Wendy J. Dahl (EDIS)
This publication addresses the characteristics, health and nutrition implications, and medical nutrition therapy recommendations for Avoidant/Restrictive Food Intake Disorder (ARFID). Written by Lily Tucciarone, Sara Murphy, and Wendy J. Dahl, and published by the UF/IFAS Food Science and Human Nutrition Department, December 2022.